1. Tìm x
\(-\dfrac{3}{5}-x=-0,75\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(-\dfrac{3}{5}-x=-0,75\)
\(\Rightarrow-\dfrac{3}{5}-x=-\dfrac{3}{4}\)
\(\Rightarrow x=\dfrac{3}{4}-\dfrac{3}{5}\)
\(\Rightarrow x=\dfrac{15}{20}-\dfrac{12}{20}=\dfrac{8}{20}=\dfrac{2}{5}\)
b) \(1\dfrac{4}{5}=-0,15-x\)
\(\Rightarrow\dfrac{9}{5}=-\dfrac{3}{20}-x\)
\(\Rightarrow x=-\dfrac{3}{20}-\dfrac{9}{5}\)
\(\Rightarrow x=-\dfrac{3}{20}-\dfrac{36}{20}=-\dfrac{39}{20}\)
c) \(x+\dfrac{1}{3}=\dfrac{2}{5}-\left(-\dfrac{1}{3}\right)\)
\(\Rightarrow x+\dfrac{1}{3}=\dfrac{2}{5}+\dfrac{1}{3}\)
\(\Rightarrow x=\dfrac{2}{5}+\dfrac{1}{3}-\dfrac{1}{3}=\dfrac{2}{5}\)
a) \(-\dfrac{3}{5}-x=-0,75\)
\(x=-\dfrac{3}{5}+0,75=\dfrac{3}{5}+\dfrac{3}{4}\)
\(x=\dfrac{27}{20}\)
________
b) \(1\dfrac{4}{5}=-0,15-x\)
\(=>-0,15-x=\dfrac{9}{5}\)
\(x=\dfrac{-3}{20}-\dfrac{9}{5}=\dfrac{-3}{20}-\dfrac{36}{20}\)
\(x=\dfrac{-39}{20}\)
c) \(x+\dfrac{1}{3}=\dfrac{2}{5}-\left(-\dfrac{1}{3}\right)=\dfrac{6}{15}+\dfrac{5}{15}\)
\(x+\dfrac{1}{3}=\dfrac{11}{15}\)
\(x=\dfrac{11}{15}-\dfrac{1}{3}=\dfrac{11}{15}-\dfrac{5}{15}\)
\(x=\dfrac{6}{15}=\dfrac{2}{5}\)
\(a,-\dfrac{3}{5}-x=-0,75\\ -\dfrac{3}{5}-x=-\dfrac{3}{4}\\ x=-\dfrac{3}{5}-\left(-\dfrac{3}{4}\right)\\ x=-\dfrac{3}{5}+\dfrac{3}{4}=\dfrac{3}{20}\\ ---\\ b,1\dfrac{4}{5}=-0,15-x\\ \dfrac{9}{5}=-\dfrac{3}{20}-x\\ x=-\dfrac{3}{20}-\dfrac{9}{5}\\ x=-\dfrac{3}{20}-\dfrac{36}{20}\\ x=-\dfrac{39}{20}\\ ----\\ c,2\dfrac{1}{2}-x+\dfrac{4}{5}=\dfrac{2}{3}-\left(-\dfrac{4}{7}\right)\\ \dfrac{5}{2}-x+\dfrac{4}{5}=\dfrac{2}{3}+\dfrac{4}{7}\\ \dfrac{33}{10}-x=\dfrac{26}{21}\\ x=\dfrac{33}{10}-\dfrac{26}{21}\\ x=\dfrac{433}{210}\)
a: \(\left(\dfrac{3}{4}x+2\dfrac{1}{2}\right)\cdot\dfrac{-2}{3}=\dfrac{1}{8}\)
=>\(\left(\dfrac{3}{4}x+\dfrac{5}{2}\right)=\dfrac{1}{8}:\dfrac{-2}{3}=\dfrac{-3}{16}\)
=>\(\dfrac{3}{4}x=-\dfrac{3}{16}-\dfrac{5}{2}=-\dfrac{3}{16}-\dfrac{40}{16}=-\dfrac{43}{16}\)
=>\(x=-\dfrac{43}{16}:\dfrac{3}{4}=\dfrac{-43}{16}\cdot\dfrac{4}{3}=\dfrac{-43}{12}\)
b: \(\dfrac{1}{3}\cdot x-0,5x=0,75\)
=>\(x\left(\dfrac{1}{3}-\dfrac{1}{2}\right)=0,75\)
=>\(x\cdot\dfrac{-1}{6}=0,75\)
=>\(x=-0,75\cdot6=-4,5\)
\(\Leftrightarrow\left(\dfrac{-3}{4}x+\dfrac{5}{2}\right)\cdot\dfrac{4}{7}=\dfrac{-5}{6}-\dfrac{1}{3}=\dfrac{-4}{3}\)
\(\Leftrightarrow-\dfrac{3}{4}x+\dfrac{5}{2}=\dfrac{-4}{3}:\dfrac{4}{7}=\dfrac{-7}{3}\)
=>-3/4x=-29/6
hay x=58/9
\(-1\dfrac{1}{2}-x=\dfrac{-2}{3}+0,75\)
\(\dfrac{-3}{2}-x=\dfrac{1}{12}\Rightarrow x=\dfrac{-19}{12}\)
\(\left|\dfrac{4}{5}-x\right|-\dfrac{1}{10}=\dfrac{2}{5}\)
\(\Leftrightarrow\left|\dfrac{4}{5}-x\right|=\dfrac{1}{2}\)
\(\Leftrightarrow\dfrac{4}{5}-x=\dfrac{1}{2}\Rightarrow x=\dfrac{3}{10}\)
\(\Leftrightarrow\dfrac{4}{5}-x=-\dfrac{1}{2}\Rightarrow x=\dfrac{13}{10}\)
1) 2,75 - 5/6 × 2/5 = 2,75 - (5/6) × (2/5) = 2,75 - 1/3 = 2,75 - 0,33 = 2,42
2) 1,25 - (5/6 - 0,75) - 3/5 = 1,25 - (5/6 - 0,75) - 3/5 = 1,25 - (5/6 - 3/4) - 3/5 = 1,25 - (5/6 - 9/12) - 3/5 = 1,25 - (10/12 - 9/12) - 3/5 = 1,25 - 1/12 - 3/5 = 1,25 - 0,08 - 0,6 = 1,25 - 0,68 = 0,57
3) 4/9 × 0,75 + 8/5 + 3,125 = (4/9) × 0,75 + 8/5 + 3,125 = 0,44 + 8/5 + 3,125 = 0,44 + 1,6 + 3,125 = 0,44 + 4,725 = 5,165
4) 1,125 - 4/7 - 0,12 = 1,125 - (4/7) - 0,12 = 1,125 - 0,57 - 0,12 = 0,435 - 0,12 = 0,315
5) (1/3 + 0,4) × 3,5 + (1/6 + 0,75) × 6/5
\(-\dfrac{3}{5}-x=-0.75\)
\(\Leftrightarrow x=\dfrac{3}{4}-\dfrac{3}{5}=\dfrac{3}{20}\)
Giúp mình với